2018
DOI: 10.1007/s10815-018-1235-0
|View full text |Cite
|
Sign up to set email alerts
|

Hippo signaling in the ovary and polycystic ovarian syndrome

Abstract: Aberrant Hippo signaling in PCOS patients is likely a contributing mechanism to the multifactorial etiology of the disease. Given the challenge of discerning the underlying etiology of oligo-ovulation in some patients, especially those with normal body mass indices, and the need for customized stimulation protocols for PCOS patients who have an increased risk of over-response and higher percentage of immature oocyte yield, it is important to identify these patients prior to treatment. Hippo gene expression fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 47 publications
0
22
0
Order By: Relevance
“…For example, organ growth depends on a series of cell biological processes, including cell proliferation, cell division, and programmed cell death. Hippo signaling pathway inhibits cell proliferation and induces apoptosis [28], which is becoming increasingly important in the study of uncontrolled cell division in cancer. The notably enriched mRNAs in Hippo signaling pathway included WNT5A, DLG4, LEF1, TEAD2, PARD6G, FZD2, BMP7, WNT6, TCF7L1, FZD7, and BMP6.…”
Section: Resultsmentioning
confidence: 99%
“…For example, organ growth depends on a series of cell biological processes, including cell proliferation, cell division, and programmed cell death. Hippo signaling pathway inhibits cell proliferation and induces apoptosis [28], which is becoming increasingly important in the study of uncontrolled cell division in cancer. The notably enriched mRNAs in Hippo signaling pathway included WNT5A, DLG4, LEF1, TEAD2, PARD6G, FZD2, BMP7, WNT6, TCF7L1, FZD7, and BMP6.…”
Section: Resultsmentioning
confidence: 99%
“…TAZ also contains a WW domain as the Yes-associated protein (YAP1) 43 and is another gene that was associated with PCOS 12, 13, 16 . WWTR1 and YAP1 are two key molecules of the Hippo signaling pathway, and their expression were significantly altered in PCOS tissues 44 . Insulin resistance affects 50-70% of women with PCOS 45 .…”
Section: Results and Implicationsmentioning
confidence: 99%
“…In patients with POI, the few existing primordial follicles would be located very close to the medulla ( 36 ). Moreover, in patients with PCOS it has been demonstrated that all pre antral follicles are trapped in cortex which could be explained by an aberrant Hippo-signaling, considered important for adequate follicular growth ( 37 ).…”
Section: Mechanical Signaling In Ovarian Functionmentioning
confidence: 99%